Observations of Arctic low-level mixed-phase clouds at Ny-Ålesund: Characterization and insights gained by high-resolution Doppler radar - Gierens, Rosa (2021)
Low-level mixed-phase clouds (MPCs) play an important role in the Arctic climate system by contributing to the surface warming. The complexities of the mixed-phase microphysics combined with the multitude of ways the low-level MPCs interact with the surface and the boundary layer make these clouds difficult to represent in climate models, which contributes to the uncertainties in predicting future climate change in the Arctic. Observations are needed to provide constrains for model parameterizations on one hand, and to improve process understanding on the other hand. However, continuous observations in the high Arctic are sparse, particularly on the eastern hemisphere. This dissertation presents the first work investigating a multi-year dataset of remote sensing observations of persistent low-level mixed-phase clouds (P-MPC) above Ny-Ålesund, Svalbard. A state-of-the-art Doppler cloud radar providing highly vertically and temporally resolved cloud measurements was utilized in combination with further remote sensing and standard meteorological observations. Two complimentary approaches for addressing the observational gaps in measuring Arctic low-level mixed-phase clouds have been considered. The first study investigated the P-MPCs above Ny-Ålesund in the context of the complex fjord environment. The occurrence and properties of P-MPC in different seasons and under different regional free-tropospheric and surface wind conditions were analyzed. Furthermore, the influence of thermodynamical coupling with the surface was investigated considering both its effect on cloud properties and how coupling is related to the local wind in the fjord. P-MPCs were found to occur most commonly with westerly winds (from the direction of the sea), and these clouds had a lower liquid base height and higher mean liquid and ice water paths compared to the clouds associated with easterly winds (from the direction of the interior of the island). The increased height and rarity of P-MPCs with easterly free-tropospheric winds suggest the ...